Interaction of Catechol‐O‐methyltransferase Val158Met polymorphism and sex influences association of parietal intrinsic functional connectivity and immediate verbal memory. Issue 10 (8th August 2020) - Wu, Sichu; Upadhyay, Neeraj; Lu, Jiaming; Jiang, Xueyan; Li, Shumei; Qing, Zhao; Wang, Junxia; Liang, Xue; Zhang, Xin; Zhang, Bing
Abstract: Introduction: Sex differences modulate catechol‐O‐methyltransferase (COMT) genotype effect at a synaptic dopamine level, which influences brain function as well as cognitive performance. In this study, we investigated how COMT Val 158 Met polymorphism and sex affect intrinsic functional connectivity and memory. Methods: Intrinsic functional networks were extracted using independent component analysis of resting‐state functional magnetic resonance imaging data from 186 healthy young COMT‐genotyped participants. The association of these functional networks and memory function was tested to investigate whether the effect of COMT × sex interaction influences the association of intrinsic functional connectivity and memory performance. Quadratic curve fit estimation was used to examine the relationship between functional connectivity and speculative dopamine level among groups. Results: COMT MM/MV carriers, relative to VV carriers, showed increased functional connectivity in left superior parietal lobule and right inferior frontal gyrus. Further, male MM/MV carriers showed significant higher mean functional connectivity in left inferior parietal lobule relative to male VV carriers and female MM/MV carriers, which was associated with worse immediate verbal recall performance. Additionally, the relationship between inferior parietal lobule functional connectivity and speculative dopamine level among groups fits the quadratic curve. Conclusions: These findings suggest that the interaction of COMT genotype and sex might regulate synaptic dopaminergic concentrations and influence the association of intrinsic functional connectivity and immediate verbal memory in left inferior parietal lobule. Abstract : Synaptic dopaminergic concentration in human brain influences brain function and memory performance, which can be modulated by both COMT Val158Met polymorphism and sex. To investigate how COMT and sex affect intrinsic functional connectivity and memory, we used independent component analysis to examine the influence of COMT genotype × sex interaction on association with functional networks and memory function. We found that male Met carriers, who are hypothesized to have higher dopaminergic concentrations, show higher functional connectivity in left inferior parietal lobule which is related to impaired immediate verbal recall performance, thus providing supporting evidence for the pathophysiology of schizophrenia.